2018
DOI: 10.18311/ajprhc/2018/18902
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Awareness about �Nutrition in Hypertension� among College Teachers in a Semi Urban Town of South India

Abstract: Hypertension is reported to be the fourth contributor to premature death in developed countries and the seventh in developing countries. Recent reports indicate that nearly 1 billion adults (more than a quarter of the world's population) had hypertension in 2000, and this is predicted to increase to 1.56 billion by 2025. The main aim of the study is to find out the level of knowledge of nutritional therapy in hypertension among college teachers through a structured questionnaire and to impart the necessary awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Such nutrition scales have also been introduced and validated by us about nutrition knowledge in hypertension. 9 In a community based cross sectional study of around 660 parturients by Nana et al, 10 the incidence of bad dietary practice among pregnant women in undeveloped country is 60.7%. But the yardstick was different.…”
Section: Discussionmentioning
confidence: 99%
“…Such nutrition scales have also been introduced and validated by us about nutrition knowledge in hypertension. 9 In a community based cross sectional study of around 660 parturients by Nana et al, 10 the incidence of bad dietary practice among pregnant women in undeveloped country is 60.7%. But the yardstick was different.…”
Section: Discussionmentioning
confidence: 99%
“…Present study clearly states that almost half the study population falls either in high risk or intermediate risk. Suchitra et al have also emphasized that lack of awareness would be the precipitating factor for conditions like hypertension 22 . This scenario indicates that the conduction of health education programs and awareness programs among the university non-teaching staffs is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…But they did not intervene to get awareness results. The same authors [20][21] have found a 10% overall prevalence of metabolic syndrome; however, the rate of having any metabolic anomaly was 43%, with college students exhibiting at least one constituent of metabolic syndrome. Furthermore, 14.3% of students had two major components of metabolic syndrome.…”
Section: Nutrition Education and Knowledgementioning
confidence: 99%